The role of androgens in pressure overload myocardial hypertrophy - Schafstedde, Marie; Nordmeyer, Sarah (Frontiers in Endocrinology, 2023)
Pressure overload hypertrophy (POH) of the left ventricle is a common result of diseases like arterial hypertension, aortic valve stenosis, hypertrophic obstructive cardiomyopathy or aortic coarctation and is associated with increased morbidity and mortality. Thus, many patients of any age and sex are affected and interventions and medical treatment aim to reduce or prevent POH. Testosterone and its most active metabolite Dihydrotestosterone (DHT) are well known for their anabolic effects in skeletal muscles (5-8), however, much less is known about specific effects of Testosterone onto the human myocardium, especially in pressure overload conditions. However, in the literature, there is increasing evidence that Testosterone also contributes to the development and progression of myocardial hypertrophy and that reduction of serum Testosterone levels reduces or prevents myocardial hypertrophy. This review focusses on the role of Testosterone and DHT in cardiac hypertrophy and discusses anti-androgenic medication as a possible treatment option to prevent or reduce POH and thus improve patient outcome.